Functionalization of ZnO- Epoxy nanocomposite in glass fiber and Kevlar. (2019) - Manigandan, S.; Jyothir Naga Manjari, G.; manoj, Konduru; Gunasekar, P.; Devipriya, J.; Nithya, S.
Abstract: The inorganic zinc oxide well known for its anti corrosion and dielectric property. This chapter deals about the enhancement of the both mechanical and electrical property of Kevlar and glass fiber without increasing the weight of the structure by adding the ZnO nano composites with the epoxy resin. The zinc oxide mixed well with the epoxy to increase the UV stability and the electrical property of the fiber by non covalent approach. The synthesis of zinc oxide with epoxy done by the direct mixing method under room temperature. The Kevlar and the glass fiber taken as the specimen for this study. The ZnO – Epoxy mixed together using the mechanical stirrer to give proper dispersion and adhesion without affecting the hydrophobic performance of the epoxy, the zinc oxide and epoxy are added with hardener with the ratio of 1:1:0.1.The size of zinc oxide is 60nm diameter. The results show that the mechanical property of the fiber is increased with reduction in weight of the laminate when they treated with the zinc oxide. From the plot and tables it is understood that the Kevlar performs better than the glass fiber when they treated with ZnO.